Some bacterial tRNA genes are transcribed by eukaryotic RNA polymerase III. - Folk, W R (1982)
E. coli genes for tRNAasp and tRNAtrp are transcribed by eukaryotic RNA polymerase III upon injection into nuclei of Xenopus oocytes. This indicates that some bacterial tRNA genes contain RNA polymerase III promoter sequences. We discuss evolutionary aspects of this finding.